Pre-Operative Scapular Rehabilitation for Arthroscopic Repair of Traumatic Rotator Cuff Tear: Results of a Randomized Clinical Trial - Luane Landim de Almeida; Adriano Fernando Mendes Júnior; José da Mota Neto; Leandro Furtado De Simoni; Karine Helena Souza Lopes; Paloma Carvalho Guimarães; Brenda Iasmin de Oliveira Valério; Aaron Sciascia (North American Sports Medicine Institute, 2021)
# Background Pre-operative rehabilitation aims to improve the functional capacity of the individual to enable him/her to prepare for the period of inactivity associated with the surgical procedure. # Objective To evaluate the impact of preoperative scapular rehabilitation before arthroscopic repair of traumatic rotator cuff injury, regarding pain, range of motion of the shoulder, and functional activity. # Study Design Randomized Clinical Trial (RCT) - pilot. # Methods Twenty adult individuals (age range: 47-69 years), with a diagnosis of traumatic rotator cuff tear and arthroscopic surgical repair, were randomized and allocated into two groups: experimental (EG) (n = 10) and control group (CG) (n = 10). All participants underwent preoperative rehabilitation for six weeks, consisting of mobility exercises of the cervical spine, elbow, wrist, and hand, and analgesics education. The EG also performed scapular and core stabilization exercises, which were not performed by the CG. Exercise instruction was performed by the same physiotherapist and the surgical team was blinded to group participation in the preoperative period. After arthroscopic repair, the patients followed the same protocol of postoperative rehabilitation for 16 weeks, and functional evaluation was conducted after three months and in a follow-up of at least one year. # Results Compared to the CG, the EG presented with a significant decrease in pain between the preoperative period and after one year (p < 0.05). In relation to the preoperative period, flexion and external rotation increased significantly in both groups after three months (p<0.05), and abduction was significantly higher in the EG (p < 0.05). Compared to CG, the EG presented a significantly higher SF-12 physical component after three months (48.47 vs. 40.33, p < 0.05), and a significantly lower Western Ontario Rotator Cuff Index (WORC) total after one year (85.00 vs. 1130.00, p < 0.05). # Conclusion Preoperative scapular rehabilitation had a positive impact on recovery after arthroscopic repair of traumatic rotator cuff injury, in the assessment of pain, range of motion of the shoulder, and quality of life. # Levels of Evidence Level 1